Efforts to Reduce Cigarette Smoke Exposure through Non-Smoking Area Regulation - Hidayah, Taufiq; Hadi, Hadi; Azinar, Muhammad (KEMAS: Jurnal Kesehatan Masyarakat, 2019)
Pollution caused by cigarette smoke causes health problems and even death in humans. Active smokers contribute to this. The number of smokers increases every year, including among the students. This study aimed to develop a Non-Smoking Area model in campus area. This study used quantitative approach supported by qualitative data. The population was every campus members in the Faculty of Sports Sciences, Semarang State University (UNNES). In the quantitative approach, a sample of 170 respondents was determined by accidental sampling technique. We used questionnaire as the instrument and the data obtained were analyzed by correlation test. We involved 10 respondents in Focused Group Discussion (FGD) to obtain the qualitative data. The results showed that 1) 25.88% smoked actively; 2) 91.2% knew about cigarette and its health risks; 3) 68.2% supported smoking ban regulations on campus; 4) respondents’ knowledge and attitude influenced smoking behavior; 5) promotional messages about the dangers of cigarettes on health must be campaigned in a communicative and effective language at a strategic location; 6) Written regulation from campus officials is critical to strengthen the implementation of No Smoking Area policy on campus.